2022
DOI: 10.1002/msc.1676
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking community/primary care musculoskeletal services: A narrative review and recommendation

Abstract: Introduction: High quality data on service performance is essential in healthcare to evidence efficacy, efficiency, and value. There remains a paucity of publicly reported data in community and primary care musculoskeletal (MSK) services. There is also a lack of guidance on which metrics MSK services should be collecting and reporting, and how this data could be used to directly improve patient outcomes, experiences, and value.Method: A narrative review of the evidence around benchmarking MSK services was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Feasibility of use of a minimal clinical dataset in busy routine clinical practice is a key consideration, but less than half (47%) of the datasets provided information on their implementation or feasibility in routine clinical care. To ensure the effective adoption of minimal clinical datasets for patients with spine-related MSK disorders in routine clinical practice, it is essential to involve all relevant stakeholders in the development process [16]. We found that 69% of the datasets engaged end-users, but healthcare professionals and patients were only involved in 50% and 28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feasibility of use of a minimal clinical dataset in busy routine clinical practice is a key consideration, but less than half (47%) of the datasets provided information on their implementation or feasibility in routine clinical care. To ensure the effective adoption of minimal clinical datasets for patients with spine-related MSK disorders in routine clinical practice, it is essential to involve all relevant stakeholders in the development process [16]. We found that 69% of the datasets engaged end-users, but healthcare professionals and patients were only involved in 50% and 28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Such a dataset should be developed to collect and compare data across different treatment pathways and bridge the gap between outcomes feasible for use in routine clinical practice, quality improvement, benchmarking, and feedback initiatives [14,15]. Engagement of patients, clinicians, and other end-users in the development process is crucial for successful implementation of minimal clinical datasets and to ensure its relevance and acceptability [16]. To be practical and to minimize response burden, they should be as brief as possible and easy to interpret [17].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this discord range from lack of clinician knowledge regarding how to advise on recommended treatments not taught in medical school to time constraints that limit their ability to delve into the psychosocial issues often associated with spine-related disorders [ 16 , 53 , 54 ]. Benchmarking and other health system-level strategies to improve care quality in musculoskeletal service delivery require additional research [ 40 , 55 ]. The prospect of changing practice habits is shown to be higher when decisions are supported by health systems with measures like payment adjustments, order restrictions, and the development of EHR integration for clinician guidance [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall the findings of this study further highlight challenges in capturing relevant, high quality musculoskeletal data. Yet in the interests of patient care, continual refinement of service metrics remains a priority to permit meaningful benchmarking (Burgess et al., 2022) not only within multi‐facility services such as the N/OPSC&MDS, but also between musculoskeletal services nationally and internationally.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation it is recommended that potential sources of variation between facilities are identified to better inform future serve planning, ensuring equitable and efficient provision of care (ACSQHC, 2013; Partington et al., 2017). This can be challenging in musculoskeletal care as systems and processes for meaningful benchmarking of musculoskeletal services are in their infancy (Burgess et al., 2022) One example of a musculoskeletal service recently reported to have variation in outcomes across its numerous facilities is the Neurosurgical and Orthopaedic Physiotherapy Screening Clinic and Multi‐disciplinary Service (N/OPSC&MDS) (Raymer et al., 2021).…”
Section: Introductionmentioning
confidence: 99%